Straw retention drives microbial community succession to improve soil C/N cycling: insights from a multi-year rice-based system - Jia, Shu; Li, Yue-Dong; Qu, Hang; Li, Bo; Juan, Ying-hua; Xing, Yue-hua; Liu, Yan; Bao, Hong-jing; Sun, Wen-tao (Frontiers in Microbiology, 2025)
The soil microbial community plays a crucial role in driving the decomposition and mineralization of plant residues, thereby affecting carbon (C) and nitrogen (N) cycling and storage. Straw retention provides soil with C and N sources, which enhances microbial community composition and nutrient cycling. While long-term straw retention has been shown to improve soil quality and nutrient-use efficiency, the impacts of short-term straw-return treatment on soil quality and the underlying microbiological mechanism of straw in improving soil fertility and nutrient-use efficiency remain unclear. The present study aimed to elucidate the dynamic responses of soil microbial community structure and function to rice straw retention using a multi-year field experiment. The findings revealed that rice straw returned for 3 and 5 consecutive years (S3 and S5, respectively), enhanced soil organic carbon (SOC) and available phosphorous (AP) contents, increased fungal biomass, and stimulated the growth of cellulose-decomposing microbial communities. Furthermore, S3 and S5 treatments increased the activities of C cycling enzymes (β-xylosidase) and N cycling enzymes (N-acetyl-glucosaminidase and urease). These treatments also increased the genes abundance associated with C-cycling (sdimo), nitrification (amoA and amoB), and N fixation (nifH), while enriched genes related to C cycling and N metabolism pathways (nitrification and nitrate reduction). In contrast, the abundance of genes involved in denitrification (nirS) was reduced. However, S3 and S5 treatments led to an increased abundance of the plant pathogens Magnaporthe oryzae and Ustilaginoidea virens. This work demonstrates that short-term straw retention effectively enhances soil microecological environment and microbial functionality and also underscores the need for strategies to mitigate pathogen accumulation for sustainable agricultural practices.